Optimum failure management strategy for periodically inspected units with imperfect maintenance. Issue 12 (2016) - Ahmadi, Alireza; Soleimanmeigouni, Iman; Block, Jan; Letot, Christophe
Abstract: The aim of this paper is to develop a reliability-based cost model for periodically inspected units subject to hidden functions, with imperfect restoration (overhaul) action after a certain number of inspections. In the model, effectiveness of the consecutive restoration actions is considered, and possible alternative maintenance strategies are identified and compared. The method is based on the Total Cost and identifies the optimum interval and frequency of inspections, as well as restoration that minimize the total life cycle cost. In the proposed model, repair due to failures found by inspection is considered as minimal repair, and restoration/overhaul action is considered as normal repair. The result also shows that for a specific value of restoration effectiveness (θ0 ), when θ> θ0, the behavior of alternatives tends to as-bad-as-old and for θ< θ0 tends to an as-good-as-new. It is also observed that when the cost of accident is high it is needed to perform inspections at smaller intervals.